(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2014)
The Law for the Self-Government of Terengganu, or Iqtanal-Muluk bi Ta’dil al-Suluk was written to strengthen the position of the King and Islam and to resist the influence of British colonial powers in the state of Terengganu. This law is regarded as a constitution for the state because of its generality that can be interpreted as meeting the requirements of an Islamic state constitution. The reason for drawing up this important document in the context of the State was the result of a conscious awareness to save Terengganu from the directly or indirectly from British control.This paper seeks to examine the assertion of sovereignty in Iqtanul Muluk for the nation-state of Terengganu and maintaining the position of the Malay Muslims. This study was conducted using library research, which includes the gathering and collecting of relevant literature, and data from documents such as the text of the Law for Self-Government of Terengganu and royal seals from the National Archives of Malaysia in Kuala Lumpur and the Terengganu branch, as well as the Museum of Terengganu. Using the method of historical research, the text of Itqanul Muluk was carefully analyzed to determine the nation-state sovereignty of Terengganu, which preserved the status of the Malay Muslims in the state. Overall, the research reveals that Itqanul Muluk was successful in preventing Terengganu from being completely overpowered by the British to the extent that a strong Malay and Muslim identity is still felt in the state till today. Keywords: Law for Self-Government of Terengganu, Melayuiyah, Islamiyah, Islamic constitution, Malay-Muslim government, British influence